Current Population Survey: Voter Supplement File, 1992 ([Verlag nicht ermittelbar], 1995)
This survey provides data on labor force activity for the week prior to the survey. Comprehensive data are available on the employment status, occupation, and industry of persons 15 years old and over. Personal characteristics such as age, sex, race, marital status, veteran status, household relationships, educational background, and Hispanic origin are also provided. Questions unique to this supplement pertain to citizenship, voting status, and registration status and were asked of respondents aged 18 or older. Data on telephone availability are also included.